Technology-Enhanced Vocabulary Learning: The Use of Canva and Quizizz in PrimaryEducation - Madhulika Sevwandi Dissanayaka; Agus Setiawan (English Education Program Universitas Pendidikan Muhammadiyah Sorong, 2025)
This study investigates the effectiveness of integrating Canva and Quizizz as technology-enhanced learning tools to improve English vocabulary mastery among fifth-grade students at SD Inpres 14 Kabupaten Sorong. The study employed a quantitative approach using a pre-experimental one-group pretest–posttest design. The participants consisted of 11 students who participated in six learning sessions using Canva-based instructional materials and Quizizz as a gamified assessment tool. Data were collected through vocabulary tests administered before and after the instructional intervention. The test consisted of 20 items, including multiple-choice and matching questions designed to measure students’ vocabulary knowledge. The results showed a clear improvement in students’ vocabulary performance after the implementation of the learning strategy. The mean score increased from 44.55 in the pretest to 70.00 in the posttest, indicating a substantial improvement in students’ vocabulary mastery. The N-Gain score of 0.45 suggests that the intervention had a moderate level of effectiveness in improving students’ vocabulary learning outcomes. These findings indicate that the integration of Canva and Quizizz can create a more engaging and interactive learning environment for young learners. Canva supports vocabulary learning through visually rich instructional materials, while Quizizz reinforces learning through gamified practice and immediate feedback. The combination of visual presentation and interactive assessment helps students retain vocabulary more effectively and increases their participation during the learning process. Therefore, Canva and Quizizz can be considered practical and effective digital tools for supporting vocabulary instruction in elementary EFL classrooms.